AGRICULTURAL ASSETS INFLUENCE ON BUILDING FARMERS RESILIENCE IN ROMANIA. FOOD SECURITY APPROACHES - Andreea Ion, Raluca; Ilie, Marinela; George-Popescu, Cristian; Daniela, Popa (Economics of Agriculture, 2021)
An increasing number of scientific papers has been written on the topic of resilience. It explains the way individuals and regions face to shocks and stressors. It focuses on farmers resilience and food security. The main shocks related to food insecurity are weather variability, volatility, and agricultural assets. We assume that the level of assets plays a role in assessing the risk level of individuals exposure to shocks and stressors. The case of Romania is discussed, using statistical data concerning land, machineries and livestock, as main agricultural assets. The data have been analyzed using simple regression model. The results show medium influences of the agricultural assets on food supply. Significant influences have registered in macro region four: West and South-West, for land, machineries and swine. The results can be used in political frameworks and strategies and to widening the knowledge in the field of farmers resilience.